Chronic myeloid leukemia with soft tissue infiltration: a case report (Faculty of Medicine Universitas Indonesia, 2015)
A 27 year old male patient with chronic myeloid leukemia under irregular hydroxyurea treatment presented with a left thigh swelling associated with a dull aching pain. Blood examination revealed a total leukocyte count [TLC] of 125,000/mm3 with 13% metamyelocytes, 8% myelocytes, 1% promyelocytes and 3% band cells. A fine needle aspiration biopsy of the swelling revealed mostly myeloblasts with occasional promyelocytes. He was maintained on tablet hydroxyurea 2g given in divided daily doses along with allopurinol, systemic alkaliser and plenty of oral fluids. Gradual symptomatic relief was achieved over next 2 months with no palpable lump after 3.5 months. TLC was 38,400/mm3 with 1% promyelocytes and myeloblasts and 5% band form. There was reduction in the liver size during this period but no reduction in spleen size. He is currently being maintained on hydroxyurea 2g with other supportive care and has not had any recurrence of symptoms for the last 9 months.